Murtadha Muthahhari Ecological Vision: Unveiling the Spiritual Foundation of Harmony Between Humans and Nature in Islamic Ecology - Firnando, Hero Gefthi (HUMANIKA, 2023)
Murtadha Muthahhari, a philosopher and theologian, offers an "eco-spiritual insight" on the worsening environmental crisis. He believes the environmental problem is spiritual, caused by humanity's disconnect from nature, leading to its exploitation. Muthahhari proposes an awakening to our interconnectedness with all life forms, stressing a new understanding of our role in the natural world. He draws from Islamic teachings, emphasizing stewardship, arguing that humans are caretakers, not masters, responsible for preserving nature's balance. His vision challenges the human-centered view and suggests a more sustainable relationship between humans and the environment.Additionally, in the abstract, the research aims to explore and elucidate Muthahhari's eco-spiritual insight as a transformative framework for addressing the environmental crisis. The objectives include analyzing Muthahhari's concept of eco-spiritual insight, examining its roots in Islamic teachings, and evaluating its potential impact on reshaping humanity's relationship with the environment. Methodologically, the research involves a comprehensive literature review of Muthahhari's works, particularly focusing on his writings related to eco-spirituality and environmental ethics. Additionally, it includes an analysis of Islamic teachings that form the basis of Muthahhari's perspective. The research employs qualitative methods to interpret and synthesize Muthahhari's ideas, providing a deep understanding of the eco-spiritual insight he advocates. The results of the research showcase the significance of Muthahhari's eco-spiritual insight in offering a unique approach to environmentalism. The formulation of results emphasizes the reawakening of spiritual consciousness, the need for a new ontology, and the concept of khalifah as pivotal elements in fostering a more sustainable and harmonious relationship between humanity and the natural world. The study concludes by highlighting the potential of Muthahhari's eco-spiritual vision to inspire a paradigm shift in environmental discourse and action.